Kebijakan Penanganan Pengungsi Luar Negeri di Indonesia - penny naluria utami; Okky Chahyo Nugroho; Donny Michael Situmorang (Inovasi, 2021)
Refugees occur because of deteriorating conditions in the political, economic, and social sphere of a country, forcing people to leave the country and seek safer shelter in other countries. Problems raised regarding the Implementation of Presidential Regulation Number 125 of 2016 concerning Handling of Refugees from Overseas and its obstacles. Identify the problems faced in implementing Presidential Regulation both structural and technical and offer a number of solutions or alternative solutions to the problems faced as outlined in the recommendations. Descriptive using a qualitative approach in order to explain the process, the parties involved and the context of implementation in field. However, challenges and problems were still found. The four factors that are the main requirements for the success of the implementation process, namely: the need for communication between tasks and functions of the Refugee Resolve Desk, shelter facilities and infrastructure in accordance with Presidential Regulation. Human resources and the budget of each stakeholder, tasks and functions of each desk which is translated into the implementing rules. Keywords: Implementation, Resolve, Refugees, Foreign.